EMERGENCE OF UZBEK FOLK INSTRUMENTAL INSTRUMENTS - Berdiyeva Dilobar (Journals Park Publishing, 2022)
This article discusses the emergence of Uzbek folk instruments. The author clarifies the problem on the basis of available scientific literature, relying on cultural data and written sources. He made a comparative analysis of the existing approaches and theories of the emergence of Uzbek folk instruments.
Keywords: Instruments; dust; flute